Meningkatkan Pemahaman Masyarakat tentang Program TOSS TB dalam Penemuan Kasus dan Pengobatan Tuberkulosis melalui Intervensi Edukasi di Puskesmas - Zita Atzmardina; Fanny Chandra; Fanya Felicia Nadin Latumahina; Joseph Wilson; Shita Chandni (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Tuberculosis (TB) is an infectious disease caused by infection with bacteria from the Mycobacterium tuberculosis complex group. TB prevention efforts are crucial, especially for individuals at high risk of exposure, to disrupt the chain of transmission of this disease. The intervention aimed to increase community understanding of TOSS TB (Find, Treat, Treat Until Cured) so that it can be applied in daily life. It is expected that after the intervention, participants' knowledge will increase, as will their ability to demonstrate the practices taught appropriately. Data collection was conducted through a mini-survey of the community in the local Community Health Center (Puskesmas) working area. The data obtained were then analyzed using the Blum Paradigm to identify factors contributing to the problem. Problem prioritization was carried out using the non-scoring Delphi method, while root cause analysis was conducted using a fishbone diagram. During the intervention process, pre- and post-tests were conducted to evaluate changes in the level of knowledge of villagers before and after the intervention. For program monitoring and evaluation, the PDCA (Plan-Do-Check-Act) cycle approach and a systems approach were used. The analysis using the Blum Paradigm showed that lifestyle was the primary contributing factor to the problem. After the intervention, three participants were able to repeat the material effectively, demonstrating a better understanding of TB prevention. Based on these results, it can be concluded that the intervention was successful and is expected to encourage improvements in public health in the village. Furthermore, this program is also expected to serve as a model for other public health interventions, thereby expanding the positive impact of TB control efforts in other areas. Thus, public awareness and knowledge about TB can continue to increase, which in turn will contribute to reducing TB incidence in Indonesia and improving the overall quality of life of the community.